A cultura pianística em São Paulo: um recorte da memória urbana (1890-1914) - Borges, Aline Maia (2019)
This research presents a view over the onset and development of the piano culture in Sao Paulo during the end of the 19th century and the beginning of the 20th century from the analysis of the depictions of the piano in journals from the referred time. It was taken into consideration that the practices related to the piano – playing, listening, composing and studying – were inserted within the classical music scenario in Sao Paulo’s capital, interacting with the city’s commercial, social and cultural practices. Through advertising, scores, concert programs, reviews and tutors’ records, it is possible to locate places, individuals and practices related to the instrument. Throughout the 19th century and the beginning of the 20th century, the piano culture was developed in the domestic environment and stages around the city, being experienced in situations of concert and learning